Necroptosis in bacterial infections - Yu, Xing; Yuan, Jin; Shi, Linxi; Dai, Shuying; Yue, Lei; Yan, Min (Frontiers in Immunology, 2024)
Necroptosis, a recently discovered form of cell-programmed death that is distinct from apoptosis, has been confirmed to play a significant role in the pathogenesis of bacterial infections in various animal models. Necroptosis is advantageous to the host, but in some cases, it can be detrimental. To understand the impact of necroptosis on the pathogenesis of bacterial infections, we described the roles and molecular mechanisms of necroptosis caused by different bacterial infections in this review.